POTENTIALITIES FOR THERAPEUTIC PURPOSES OF THE BIOGENIC CARBONATE SAND OCCURRING IN SOME ISLANDS OF THE MACARONESIA ARCHIPELAGO BASED ON THEIR UNIQUE CHEMICAL AND PHYSICAL PROPERTIES - Gomes, C. S. F.; Silva, J. B. P.; Sequeira, M. C.; Gomes, J. H (Geochimica Brasiliensis, 2012)